(untitled) (International Journal of Food and Nutritional Sciences, 2022)
However, visitor diseases become personal and personal diseases also turn into visitor diseases. Similarly, mental and physical diseases can also be interchangeable. In this way, physical and mental disorders affect each other. It is for this purpose that Ayurveda has adopted a holistic psychological approach from the beginning. Acharya Charaka has specified the interplay of body and essence. The same principle is visible everywhere, from the body to the body, to the nature and disease. Ayurveda is the science of age, science of life is- Jeeva = Sattva + Soul + Body is a combination of Therefore, in every disorder, it is natural for the Sattvatmashir to be affected. Nevertheless, with the best distinction, some diseases are considered physical and some mental and some in the spiritual category. Therefore, diseases in which mainly mental disorder occurs and symptoms are mainly mental rather than physical are called diseases. Like - Mania, epilepsy, abstinence, etc. On the contrary, diseases which arise due to mental reasons and their expression is predominantly physical are called psychiatric diseases. Finally main intention for presenting this paper is to share basic details of Causes of Manasvikar as proper Treatment.